Raising an ADHD child : relations between parental stress, child functional impairment, and subtypes of the disorder - Cheesman, Jessica (Department of Psychology, 2014)
The broad aim of this study was to gain a clear picture of how mothers of children with ADHD experience stress, how their stress levels compare to those of mothers of children without ADHD, and which factors predict the extent to which they are stressed.